Preventing accidents in India-can educational intervention to medical students work? Outcomes of a quasi-experimental study - Dave, Sanjev; Dave, Anuradha; Pant, Bhawna; Thakur, Nidhi; Roy, Priya; Singh, Puja; Bhatt, Punit; Rajendra, Sankhe Arya (International Journal Of Community Medicine And Public Health, 2025)
Background: As per world health organization (WHO) report an accident-related deaths are known to be the eighth leading cause of death and first largest cause of death among children aged 5-14 years and adults aged 15-29 years. As most of the deaths due to road traffic accidents (RTA) were among younger people. So, prevention of RTAs is very crucial by creating awareness and taking proper measures toward road safety in young adults like medical students. The aim of the study was therefore to explore the knowledge, attitude and practices regarding the road safety regulations among medical college students of private medical college in Meerut. Methods: Study setting was in private medical college in Meerut, study population was 150 medical students, study unit was 150 undergraduate medical students of Batch 2021 and 2022, study design used was: Ani experimental study sample size: complete enumeration sampling technique (purposive sampling) inclusion criteria included all those who are present at the time of data collection. Data analysis was done by structured questionnaire on google form MS excel with appropriate test. Results: For all informative, warning and imperative signs the knowledge, attitude, and practice (KAP) were significantly improved (p<0.05 in each case) after giving educational intervention on road safety signs. Conclusions: There was significant improvement in the knowledge attitude, practices of medical students after educational intervention on road safety regulations, so this approach can help in reduction of RTA incidents in India, which can be studied also in future studies.